STM Characterization of Phenylene-Ethynylene Oligomers on Au(111) and their Integration into Carbon Nanotube Nanogaps - Thiele, Cornelius (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2014)
Molecular electronics requires both profound knowledge of a molecule's structure and functionality on a surface and controlled positioning between electrodes with nanometer-sized gaps. In the first part of this work, a detailed scanning tunneling microscope study of two variants of oligo(phenylene ethynylene) molecules is presented. In the second part, methods of fabricating carbon nanotube nanogap electrodes as direct contacts to these molecules are explored.